Concurrent Presentation of Hodgkin Lymphoma and Multiple Myeloma. (19th August 2013) - Chandran, Rekha; Simon, Miklos; Spurgeon, Stephen E.
Abstract : The simultaneous presentation of the Hodgkin lymphoma and multiple myeloma in the absence of prior chemotherapy or radiation is very rare. Here, we discuss a 72-year-old patient who initially presented with generalized pruritis. Workup led to a diagnosis of multiple myeloma which progressed and required treatment. As part of his pretreatment workup, an MRI was performed to evaluate skeletal lesions. This revealed diffuse and bulky adenopathy which was confirmed by PET. A biopsy of an axillary node was consistent with the nodular sclerosing type Hodgkin lymphoma. He was treated with adriamycin, bleomycin, vinblastine, and dacarbazine (ABVD) chemotherapy × 6 resulting in complete resolution of his adenopathy and pruritis as well as improvement in his myeloma.